Application Effect of Whole-Process Seamless Nursing Model Based on Smart Healthcare Mode in Perioperative Period of Patients Undergoing Hematoma Removal. (23rd February 2022) - Liu, Chang; Liu, Rui; Li, Zhaohua; Tang, Meiling; Wang, Fenghua
Abstract : Objective . To explore the application effect of a whole-process seamless nursing model based on the smart healthcare mode in the perioperative period of patients undergoing hematoma removal. Methods . In this retrospective study, 50 patients with hematoma removal admitted to our hospital from August 2018 to August 2019 were included as the control group (CG), while 50 patients with hematoma removal admitted to our hospital from September 2019 to September 2020 were included as the experimental group (EG). During the period of hematoma removal, CG received routine perioperative nursing, while EG received the whole-process seamless nursing model based on the smart healthcare mode. The perioperative indexes, hemodynamic indexes, and the incidence of postoperative complications were compared between the two groups, and the incidence of nursing staff's work omissions in different periods was analyzed. Results . Notable differences were observed in surgical time, intraoperative blood loss, hematoma clearance rates, length of ICU stay, hospitalization time, removal time of ventricular drainage tube, and cerebral edema volume at 1 week after surgery between EG and CG ( P < 0.05). Compared with CG, EG achieved obviously better hemodynamic indexes ( P < 0.001) and a lower incidence of bedsore, muscle atrophy, and eating/swallowing disorders ( P < 0.05). During the implementation of smart healthcare, the incidence of nursing staff's work omissions was remarkably reduced ( P < 0.05). Conclusion . Under the smart healthcare, the incidence of nursing staff's work omissions is lower, and the effect of the whole-process seamless nursing is better, which can optimize the perioperative indexes of patients, stabilize the postoperative hemodynamics, and reduce the incidence of complications. Therefore, the whole-process seamless nursing model based on the smart healthcare mode has promotion value in clinic.